2003
DOI: 10.1095/biolreprod.103.015925
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Seminiferous Epithelium in Primates: Relationship to Spermatogenic Efficiency, Phylogeny, and Mating System1

Abstract: The succession in time and space of specific germ cell associations, denoted as spermatogenic stages, is a typical feature of mammalian spermatogenesis. The arrangement of these stages is either single stage (one spermatogenic stage per tubular cross-section) or multistage (more than one spermatogenic stage per tubular cross-section). It has been proposed that the single-stage versus multistage arrangement is related to spermatogenic efficiency and that the multistage arrangement is typical for hominids. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 38 publications
3
82
3
Order By: Relevance
“…Further studies are needed to determine if the inclusion of intronic sequences such as those seen in the macaque are replicated in other species. Interestingly, studies on the organisation of spermatogenesis in primate species have revealed that the marmoset more closely resembles the human than does the macaque , Wistuba et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to determine if the inclusion of intronic sequences such as those seen in the macaque are replicated in other species. Interestingly, studies on the organisation of spermatogenesis in primate species have revealed that the marmoset more closely resembles the human than does the macaque , Wistuba et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a common hallmark of human and marmoset testes is that gonocytes are still present in the testes of a newborn until a couple of weeks after birth (Wistuba et al, 2003;Mitchell et al, 2008). This is in contrast to testes from newborn rhesus and cynomolgus monkeys, which contain type A spermatogonia as the predominant germ cell type (Simorangkir et al, 2005).…”
Section: Animal Models To Study Early Germ Cell Development In the Humanmentioning
confidence: 99%
“…First, the marmoset shows early sexual maturity (at around 1 year of age) and produces many offspring throughout its lifespan, which can provide researchers with much material and many opportunities for routine experiments. Secondly, marmoset testicular development is similar to that of humans (Millar et al 2000, Wistuba et al 2003, Li et al 2005, Mitchell et al 2008; for example, marmoset and human testes retain gonocytes even in newborns, but their persistence has not been observed in rhesus or cynomolgus monkeys (Wistuba et al 2004, Simorangkir et al 2005, Mitchell et al 2008, Albert et al 2010). Thirdly, it is possible to generate transgenic marmosets with germline transmission by lentiviral gene transduction ).…”
Section: Molecular Signature Of Marmoset Spermatogenesismentioning
confidence: 99%
“…In adults, as in other mammals, spermatogenesis undergoes proliferative, meiotic, and spermiogenic phases to produce sperm (for review, see Li et al (2005)). Although the number of mitotic steps during spermatogenesis differs between marmoset and human (Millar et al 2000, Ehmcke et al 2006, they share many similarities in the organization and sequence of spermatogenic processes (Millar et al 2000, Wistuba et al 2003, Li et al 2005, Mitchell et al 2008. Thus, the common marmoset appears to be an appropriate experimental animal model for human testicular germ cell development.…”
Section: Introductionmentioning
confidence: 99%